Evidence-based first aid advice for paediatric burns in the United Kingdom. Issue 3 (May 2016) - Varley, Alice; Sarginson, Julia; Young, Amber
Highlights: A lack of consistency between the content of first aid guidelines has been demonstrated in the UK. An evidence-based statement for standardised first aid advice for burns in children is reported. Adequate cooling improves patient outcomes after burn injury. Abstract: Background: Burn and scald injuries are common in children. First aid advice for paediatric burns is offered by a range of health organisations and charities in the UK. Despite this, children still present to emergency departments and burn services having received little or inadequate first aid. Method: A survey was undertaken regarding the content and consistency of the advice given by a cross-section of UK health organisations involved in first aid prevention and education. The advice was subsequently examined to determine if it was evidence-based. Results: Our study has demonstrated inconsistencies in the content of the first aid advice provided by the 21 organisations included in the study. Seventy-one percent of the information was only available online. The temperature, method and duration of cooling varied substantially, as did the advice recommended for the removal of clothing and jewellery and methods for covering the burn immediately after injury. Results from the literature review concluded the following based on available evidence; cool the burn with running tap water for 20 min, remove clothing and jewellery and cover the burn with cling film or a clean non-adhesive dressing. Conclusions: This study highlights the lack of consistency between first aid guidance provided by health organisations and charities in the UK.